Kinetic implication of moving warm side-stream Anaerobic ammonium oxidizing bacteria to cold mainstream wastewater. (September 2019) - Straka, Levi; Summers, Amanda; Stahl, David A.; Winkler, Mari K.H.
Graphical abstract: Highlights: Warm Anammox (>25 °C) were significantly impeded at cold (<15 °C) temperatures. The Arrhenius equation did not represent changes in Anammox activity consistently. The CTMI model represented changes in Anammox activity very well. Very large time and/or biomass are required for significant cold Anammox. Abstract: Decreased activity of Anaerobic ammonia oxidation (Anammox) at low temperatures is widely reported and one of the key challenges to applying Anammox to mainstream wastewater treatment. In this work, we systematically measured Anammox across a range of temperatures for biomass taken from a side-stream (25–30 °C) Anammox system. Using the Cardinal temperature model with inflection (CTMI) and parameters Tmin = 10 °C, Topt = 31 °C, Tmax = 40 °C, and µmax = 0.29 d −1, the data was accurately represented. Alternatively, the popularly used Arrhenius equation was not able to consistently capture the trend we observed. The CTMI was further used to compute the relative increase in retention time and/or biomass concentration to treat the same quantity of nitrogen at sub-optimal temperatures, requiring a two-fold increase at 21 °C and three-fold increase at 19 °C. We conclude that cold adapted cultures are necessary to evaluate the possibility of cold Anammox wastewater treatment.